The discontinuous integration of Western Europe's heterogeneous market for corporate control from 1995 to 2007 - Rainer Frey (Deutsche Bundesbank, 2010)
As, in Europe, many institutional reforms have been undertaken to establish an economic union, it can be expected that the relevance of borders has decreased over time. For the EU 15, we investigate the expected integration process of the market for corporate control - an illustrative market for studying integration issues - over the period from 1995 to 2007. Our gravity regressions show that borders lost relevance from 1995 up to the bursting of the new economy bubble. During this period, the transition from the European Economic Community to the European Union at the end of 1993 and the introduction of the euro may have led to accelerated integration. However, thereafter we find no evidence for further progress driven by institutional factors. On the other hand, geographical distance became less relevant for M&As for the entire time span from 1995 to 2007. The continued lack of full integration is also evidenced by heterogeneity inside Europe. This becomes apparent in differing and continuing bilateral border effects. Country pairs with supposedly liberal capital market thinking, such as the Netherlands, Germany and the UK are found to be divided by relatively small barriers. Hence, a still existing lack of integration in Europe may not be a result of missing institutional reforms. In the Poisson estimations, the results depend neither on the choice of the number of observations nor on the log of aggregated transaction value as the dependent variable; however, the use of the levels is inappropriate.
Keywords: F21; F23; F36; G15; G34; R12; 330; Integration; Europe; border effects; bilateral borders; distance; gravity; Poisson; panel; mergers and acquisitions; Übernahme; Marktintegration; EU-Binnenmarkt; Gravitationsmodell; Entfernung; Schätzung; EU-Staaten